Lifestyle of Farming Community in Punjab: A Major Health Determinant - Saikia, Anadi Ranjan; Mittal, Ritu (Indian Journal of Extension Education, 2022)
The health status of the farming community and the various lifestyle factors which affect the health of the farming community is still an subject matter of less importance for researchers. The present study was aimed to find out the relationship of health with lifestyle of the farming community and data were collected using survey from a sample of 120 respondents from the farming community of Punjab, India during 2021. The overall health status was measured in terms of mental health status and physical health status. The lifestyle was measured through 8 parameters i.e. dietary diversity score, meal frequency,nutrition intake, physical activity, stress management, personal health habits, availing medical advice and substance abuse. The findings revealed that lifestyle was correlated with physical health, mental health as well as overall health. The results also showed that mental health, physical health and overall health of male respondents were better than female respondents. It was inferred that health was dependent on lifestyle. Therefore, there is need to create awareness and knowledge about importance of lifestyle among farming community.